2014
DOI: 10.1007/s00281-014-0467-z
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal innate immunity: recognition and inflammatory networks

Abstract: A large variety of fungi are present in the environment, among which a proportion colonizes the human body, usually without causing any harm. However, depending on the host immune status, commensals can become opportunistic pathogens that induce diseases ranging from superficial non-harmful infection to life-threatening systemic disease. The interplay between the host and the fungal commensal flora is being orchestrated by an efficient recognition of the microorganisms, which in turn ensures a proper balance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 89 publications
2
73
0
2
Order By: Relevance
“…ILC3 cells have been shown to secrete IL-17 and IL-22 in the lungs in obesity (45), Streptococcus pneumoniae (46), and fungal infections (47,48). These ILC3 cells may modulate the long-term inflammatory response to S. chartarum, and are likely key mediators of chronic inflammatory responses (49).…”
Section: Cd3mentioning
confidence: 99%
“…ILC3 cells have been shown to secrete IL-17 and IL-22 in the lungs in obesity (45), Streptococcus pneumoniae (46), and fungal infections (47,48). These ILC3 cells may modulate the long-term inflammatory response to S. chartarum, and are likely key mediators of chronic inflammatory responses (49).…”
Section: Cd3mentioning
confidence: 99%
“…It was previously shown that galectin-3 on macrophages recognizes β-mannan from C. albicans and, in collaboration with TLR2, is able to induce protective antifungal responses via TNF-α secretion [24]. It has also been suggested that galectin-3 can have a dual role in the regulation of neutrophil function, depending on its cellular location.…”
Section: Additional Mannose-binding Lectinsmentioning
confidence: 99%
“…This interaction can modulate cytokine and ROS production, as well as fungal killing [24]. In addition, dectin-2 can induce cysteinyl leukotriene production, which has been shown to be essential for the initiation of airway inflammation and Th2 immunity against house dust mites.…”
Section: The Dectin-2 Clustermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, inside a host, defence mechanisms, such as the immune system, complicate the life of fungi, and they have to be able to counteract different host-induced stresses. A lot of reviews have been published concerning the host mechanisms of sensing fungal pathogens (Bourgeois and Kuchler, 2012;Becker et al, 2015;Sanchez-Vallet et al, 2015;Stokes et al, 2015). In contrast, we aim to give an overview on fungal sensing of a host environment.…”
Section: Introductionmentioning
confidence: 99%